The 2008 Global Financial Crisis And Its Implications In Tanzania: A Focus On Official Development Assistance (Oda) (Global Journal of Management and Business Research, 2012)
This paper is on the 2008 global financial crisis and its implications in Tanzania with a focus on Official Development Assistance (ODA). The author gives an overview of the meaning,nature,causes,impacts and possible solutions for the crisis in Tanzania in general. Informed mainly by a review of literature and experts and practitioners opinion, it is found by the author that the crisis officially started to manifest itself in September 2008 in the financial markets in the United States of America (USA). Since then it has spread not only to financial but also to the real economy to many parts of the world especially in Europe and Asia where the first round effects are rapidly being experienced. In Africa, the second round effects (bounce-on effects) are increasingly being experienced The many direct and indirect, long term and short term impacts are emanating from the global economic recession that is unfolding as a result of the crisis.There have been several strategies to deal with the crisis at macro-and micro-level in various countries. These include but are not limited to various bailout plans and stimulus packages forvarious economies in general and specific sectors and industries in particular